2016
DOI: 10.1016/j.resconrec.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater as a resource: Strategies to recover resources from Amsterdam’s wastewater

Abstract: a b s t r a c tResources are becoming scarce. Therefore, reuse of resources is becoming more and more attractive. Wastewater can be used as a resource, since it contains many resources like organic matter, phosphorus, nitrogen, heavy metals, thermal energy, etc. This study focused on the reuse of organic matter and phosphorus from Amsterdam's wastewater. There is a wide variety of possible alternatives, and the technical options are growing. The problem is not the availability of technology for resource recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(94 citation statements)
references
References 43 publications
0
92
0
2
Order By: Relevance
“…The program involves resources such as cellulose, bioplastics, phosphate, alginate-like exopolymers from aerobic granular sludge, and biomass [23]. Due to its many possibilities, the challenge is how to develop a coherent policy and strategy, and how to make the right choices [24].…”
Section: Introductionmentioning
confidence: 99%
“…The program involves resources such as cellulose, bioplastics, phosphate, alginate-like exopolymers from aerobic granular sludge, and biomass [23]. Due to its many possibilities, the challenge is how to develop a coherent policy and strategy, and how to make the right choices [24].…”
Section: Introductionmentioning
confidence: 99%
“…Так, в Україні на лічується більше 6000 насосних та більше ніж 3000 очисних споруд, з них близько 87% по требують капітального ремонту. Як наслідок, у водні об'єкти щорічно надходить близько 3,9 неочищених стічних вод, 3,3 нормативно чи стих і лише 1,3 очищених до чинних нормативів [8].…”
Section: виклад основного матеріалу дослідження з повним обгрунтуваннunclassified
“…An assessment of the energy saving potential of several integrated water management systems in Brazil found that reducing the wastewater treatment at the centralized systems was preferable (more energy saving) to using alternative water sources in terms of water sustainability (Vieira and Ghisi, 2016). van der Hoek et al (2016) successfully utilized an adaptive policymaking method to develop viable strategies regrading resource recovery in Amsterdam's wastewater chain. Three phases were involved in the method: a material flow analysis, the identification and characterization of measures (resources to be recovered), and the development of strategies to recover resources.…”
Section: Energy and Resourcesmentioning
confidence: 99%